2019
DOI: 10.1002/stem.3052
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Phosphoinositide-3-Kinase Signaling Promotes the Stem Cell State of Trophoblast

Abstract: Trophoblast stem cells (TSCs) are a heterogeneous cell population despite the presence of fibroblast growth factor (FGF) and transforming growth factor β (TGFB) as key growth factors in standard culture conditions. To understand what other signaling cascades control the stem cell state of mouse TSCs, we performed a kinase inhibitor screen and identified several novel pathways that cause TSC differentiation. Surprisingly, inhibition of phosphoinositide-3-kinase (PI3K) signaling increased the mRNA and protein ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Moreover, p110α in both the trophoblast and epiblast-derived lineages contributed to the formation of the capillary network and the thinness of the diffusion barrier in the placental exchange region. These findings are consistent with previous work demonstrating that the PI3K pathway regulates trophoblast differentiation (Kent et al, 2010; Lee et al, 2019) and defects in p110α signaling impair developmental angiogenesis and placental exchange region morphogenesis (Graupera et al, 2008; Lelievre et al, 2005; Sferruzzi-Perri et al, 2016). However, we did not find expression of any markers of known differentiated trophoblast subtypes (eg Syna, Synb, Gcm1, Ctsq ), endothelial cells (eg Pecam1 ) or angiogenesis (eg Ang1/2, Tie2, Vegf ) in placentas that lacked p110α (in the Hom-P compared to Het-U placenta by RNA-seq) thatwould explain the morphological phenotype observed.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, p110α in both the trophoblast and epiblast-derived lineages contributed to the formation of the capillary network and the thinness of the diffusion barrier in the placental exchange region. These findings are consistent with previous work demonstrating that the PI3K pathway regulates trophoblast differentiation (Kent et al, 2010; Lee et al, 2019) and defects in p110α signaling impair developmental angiogenesis and placental exchange region morphogenesis (Graupera et al, 2008; Lelievre et al, 2005; Sferruzzi-Perri et al, 2016). However, we did not find expression of any markers of known differentiated trophoblast subtypes (eg Syna, Synb, Gcm1, Ctsq ), endothelial cells (eg Pecam1 ) or angiogenesis (eg Ang1/2, Tie2, Vegf ) in placentas that lacked p110α (in the Hom-P compared to Het-U placenta by RNA-seq) thatwould explain the morphological phenotype observed.…”
Section: Discussionsupporting
confidence: 93%
“…While globally, 5hmC enrichment levels at CGIs were not strongly correlated with transcriptional activity of associated genes, there were a few notable exceptions ( Figures 2 E and S3 A). Cdx2 , a core TSC transcription factor known to be downregulated early in TSC differentiation ( Tanaka et al., 1998 , Latos et al., 2015a , Lee et al., 2019 ), lost 5hmC from a CGI associated with a putative 3′-enhancer in differentiated TSCs ( Watts et al., 2011 ). Interestingly, depletion of 5hmC was also observed at Lefty2 , a transcription factor that is similarly downregulated upon TSC differentiation ( Latos et al., 2015a ) and indeed is one of the most strongly downregulated genes in Tet1 KO TSCs ( Chrysanthou et al., 2018 ) ( Figure 2 E).…”
Section: Resultsmentioning
confidence: 99%
“…S 3 ; manuscript for the complete screen in preparation). A similar kinase inhibitor screen recently identified that several Aurora kinase inhibitors (including CCT137690, MLN8237, AT9283, and TC-A-2317) reduce CDX2 (a stem cell marker) expression in TSCs, thereby inducing their differentiation [ 43 ]. Thus, we conclude that Aurora A is required for maintaining the stemness of TSCs and inhibition of its activity results in their differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…S 3 ). A recent kinase inhibitor screen for inducers of TSC differentiation also identified Aurora kinase inhibitors including CCT137690 [ 43 ]. CDK1 activity is required for activation of Aurora A during G2/M transition [ 45 ].…”
Section: Discussionmentioning
confidence: 99%